2021
DOI: 10.1177/1460458220972750
|View full text |Cite
|
Sign up to set email alerts
|

The impact of algorithmic decision-making processes on young people’s well-being

Abstract: This study aims to capture the online experiences of young people when interacting with algorithm mediated systems and their impact on their well-being. We draw on qualitative (focus groups) and quantitative (survey) data from a total of 260 young people to bring their opinions to the forefront while eliciting discussions. The results of the study revealed the young people’s positive as well as negative experiences of using online platforms. Benefits such as convenience, entertainment and personalised search r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…To do this, ML requires an enormous amount of personal data to make accurate and meaningful predictions. The widespread use of recommendation algorithms in social media and websites have also changed how people use the internet, and algorithm-mediated personalized content is now not only widely accepted, but is increasingly how people, especially young adults [85], want to consume media and content. According to a consumer research survey, the vast majority of users are willing to share personal data in exchange for better, more relevant, and curated digital experiences [86].…”
Section: Discussionmentioning
confidence: 99%
“…To do this, ML requires an enormous amount of personal data to make accurate and meaningful predictions. The widespread use of recommendation algorithms in social media and websites have also changed how people use the internet, and algorithm-mediated personalized content is now not only widely accepted, but is increasingly how people, especially young adults [85], want to consume media and content. According to a consumer research survey, the vast majority of users are willing to share personal data in exchange for better, more relevant, and curated digital experiences [86].…”
Section: Discussionmentioning
confidence: 99%
“…Ainda assim, Büchi (2021) enfatiza que as dinâmicas da esfera macro moldam oportunidades e limites para a atuação e para o comportamento individual no meio digital. Essa noção apresenta-se como especialmente relevante no caso de crianças e adolescentes, uma vez que esses tendem a se sentir especialmente impotentes diante de aspectos estruturais do meio digital (Creswick et al, 2019;Perez Vallejos et al, 2021). No caso dos termos de uso, por exemplo, crianças relatam não serem capazes de compreendê-los por completo, acreditando que esses documentos não são escritos considerando-as como público-alvo (Creswick et al, 2019).…”
Section: Büchi: Impacto Estrutural Em Ações Individuaisunclassified
“…A literatura indica que a atual geração de jovens frequentemente se sente impotente perante as grandes estruturas digitais (Creswick et al, 2019, Perez Vallejos et al, 2021. No contexto brasileiro, uma pesquisa conduzida com jovens entre 11 e 17 anos revelou que um quarto já "[...] tentou passar menos tempo na internet, mas não conseguiu" e 16 % já "deixou de comer ou dormir por causa da internet" (CETIC, 2022).…”
Section: Introductionunclassified
“…This lack of trust is exacerbated even further among minorities and vulnerable groups. For example, one analysis revealed that reduced trust in the UK's National Health Service among black, Asian, and minority ethnic populations had an effect on the app's uptake [ 139 ]. Moreover, according to one research, immigrants in the United States fear that these applications are actually owned by police [ 140 ].…”
Section: Co-occurrence Analysis Of Abstract and Content Analysis Of T...mentioning
confidence: 99%